Clinical evidence for a biological effect of epigenetically active decitabine in relapsed or progressive rhabdoid tumors. Issue 12 (4th August 2021) - Steinbügl, Mona; Nemes, Karolina; Johann, Pascal; Kröncke, Thomas; Tüchert, Stefanie; da Costa, Maria Joao Gil; Ebinger, Martin; Schüller, Ulrich; Sehested, Astrid; Hauser, Peter; Reinhard, Harald; Sumerauer, David; et al.
Abstract: Background: Refined therapy has helped to improve survival rates in rhabdoid tumors (RT). Prognosis for patients with chemoresistant, recurrent, or progressive RT remains dismal. Although decitabine, an epigenetically active agent, has mainly been evaluated in the management of hematologic malignancies in adults, safety in children has also been demonstrated repeatedly. Materials and methods: A retrospective series of patients who received decitabine upon relapse or progression following therapy according to the EU‐RHAB regimen is presented. Due to the retrospective nature of analyses, response was defined as measurable regression of at least one lesion on imaging. 850k methylation profiling was done whenever tumor tissue was available. Results: A total of 22 patients with RT of any anatomical localization were included. Most patients (19/22) presented with metastases. All received low‐dose decitabine with or preceding conventional chemotherapy. Patients received a median of two (1‐6) courses of decitabine; 27.3% (6/22) demonstrated a radiological response. Molecular analyses revealed increased methylation levels in tumors from responders. No excessive toxicity was observed. Clinical benefits for responders included eligibility for early phase trials or local therapy. Responders showed prolonged time to progression and overall survival. Due to small sample size, statistical correction for survivorship bias demonstrated no significant effect on survival for responders. Conclusions: Patients with RT demonstrate promising signs of antitumor activity after multiagent relapse therapy including decitabine. Analyses of methylation data suggest a specific effect on an epigenetic level. We propose to consider decitabine and other epigenetic drugs as candidates for further clinical investigations in RT.